2006
DOI: 10.1042/bj20060765
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of human GTP cyclohydrolase I with its splice variants

Abstract: Tetrahydrobiopterin is an essential cofactor for aromatic amino acid hydroxylases, ether lipid oxidase and nitric oxide synthases. Its biosynthesis in mammals is regulated by the activity of the homodecameric enzyme GCH (GTP cyclohydrolase I; EC 3.5.4.16). In previous work, catalytically inactive human GCH splice variants differing from the wild-type enzyme within the last 20 C-terminal amino acids were identified. In the present study, we searched for a possible role of these splice variants. Gel filtration p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
1
12
0
2
Order By: Relevance
“…The second mechanism is through suppressing translation of full-length α ENaC more prominently in Dahl R versus S rats. The third mechanism is via an enhanced binding of α ENaC-b protein to the full-length α ENaC and accelerated degradation of the latter as a result of direct binding to α ENaC-b, a phenomenon that has been reported previously in several other channels and membrane proteins [7-9,11-13]. Enhanced binding of α ENaC-b to the full-length α ENaC might trap α ENaC in the endoplasmic reticulum and/or inhibit proper ENaC assembly and trafficking to the plasma membrane, resulting in the formation of non functional channels.…”
Section: Presentation Of the Hypothesismentioning
confidence: 86%
“…The second mechanism is through suppressing translation of full-length α ENaC more prominently in Dahl R versus S rats. The third mechanism is via an enhanced binding of α ENaC-b protein to the full-length α ENaC and accelerated degradation of the latter as a result of direct binding to α ENaC-b, a phenomenon that has been reported previously in several other channels and membrane proteins [7-9,11-13]. Enhanced binding of α ENaC-b to the full-length α ENaC might trap α ENaC in the endoplasmic reticulum and/or inhibit proper ENaC assembly and trafficking to the plasma membrane, resulting in the formation of non functional channels.…”
Section: Presentation Of the Hypothesismentioning
confidence: 86%
“…Accordingly, we hypothesize that the impaired activation of GTP cyclohydrolase may represent a consequence of postmitotic maturation of cardiac myocytes coinciding with the repression of certain unknown genes or possibly increasing levels of pertinent silencing mRNA. Alternatively, splice variants of GTP cyclohydrolase have been reported that lack functional activity, thereby functioning via a dominant negative effect (13,20,41). However, it is remains unclear whether splice variants are an operative mechanism in adult cardiac myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot was also performed under native conditions. (3) The MAb recognized non-denaturing VSTM1-Fc protein well, but only a nonspecific band could be detected in granulocytes. (4) Specific Antigen Identified …”
Section: Igg2bmentioning
confidence: 99%